Analysis of in vitro and in vivo sensitivity of oral cancer cells to methotrexate - Pai, R.B.; Lalitha, R.M.; Pai, S.B.; Kumaraswamy, S.V.; Lalitha, N.; Bhargava, M.K. (Experimental Oncology, 2009)
Aim: The present study was directed on the assessment of the response of treatment-naive oral cancer cells to methotrexate (MTX)
in vitro and clinical response to MTX therapy. Methods: A pilot study of in vitro evaluation of MTX response of oral cancer cells
from 10 patients was conducted using a cell viability assay to determine the sensitivity/resistance to MTX. Quantitative in vitro data
were correlated to the clinical outcome to MTX therapy. Results: A positive correlation was observed between the effect of MTX
on tumor cells in vitro and clinical response for 7 out of 10 patients. Conclusions: Observations from the proof-of-principle pilot
study suggests that oral cancer cells have intrinsically variable response toMTX. Confirmation ofthese findings with a larger cohort
of patients could aid in the development of individualized therapies for this class of malignancy.